(untitled) (Eurasian Journal of Philology Science and Education, 2022)
In this article we are talking about the features of the ideas of Abai Kunanbayev from the point of view of its use as the basis of the spiritual and intellectual potential of Kazakhstan. The purpose of the study is to analyze the possibility of using Abai’s ideas as the basis of the spiritual and intellectual potential of modern Kazakhstan. To achieve this goal, the following tasks were set: to characterize the main postulates of Abai’s ideas; to identify the role and place of Abai’s ideas in the spiritual and intellectual life of Kazakhstan; to analyze the possibilities of using of Abai’s ideas as one of the important foundations of the spiritual and intellectual potential of modern Kazakhstan, and especially the Kazakh youth. The following were used as the main research methods: analysis of theoretical literature on the research topic, as well as analysis of the most significant provisions of Abai’s ideas, comparative analysis, retrospective analysis, the method of generalizations (synthesis). During the research, the author came to the conclusion that Abai Kunanbayev, being one of the spiritual and intellectual leaders of Kazakhstan, was able to feel the peculiarities of the spiritual world of the Kazakhs very subtly, and to reflect the cultural code of the Kazakh ethnic group in his works. At the present time, Kazakhstan is going through a rather difficult transformational period, which requires mutual support, consent and a high level of unity from the entire Kazakh people. Throughout his life, Abai called on the Kazakh people to do so, which explains the need to appeal to his creative heritage at the present time. The spiritual and intellectual heritage of Abai Kunanbayev has a positive impact on the modernization of the public consciousness of the Kazakh society, and makes an invaluable contribution to strengthening stability, unity, mutual understanding and trust in the Kazakh society. One of the most significant achievements of Abai in the framework of his activities in the field of education is the development of self-awareness of Kazakhs, the intelligentsia of Kazakhstan, as well as education and science in the state.